Penerapan Teknik Pengambilan Gambar pada Produksi Video Feature “Tangan Kecil, Pena Besar” - Anggi Talisa Permatasari Siahaan; Kokom Komariah; Gumgum Gumilar (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
A feature video is an audiovisual work designed to convey information through a narrative and emotional approach. In this final project, the author highlights the issue of education for street children through a feature video titled "Tangan Kecil, Pena Besar". The Author served as the Director of Photography (DOP), focusing on the application of cinematographic techniques to enhance visual quality and message delivery. The purpose of this project is to explain the techniques of cinematography, including type of shot, camera angle, camera movement, and lighting. The creation process consists of three stages, pre-production (brainstorming, storyboard and shot list development), production (filming interviews and activity scenes), and post-production (editing and visual finalization). The type of shot technique is used to frame subjects in various sizes, camera angles provide specific viewpoints to shape visual perception; camera movement helps create dramatic mood and atmosphere, while lighting is applied to illuminate subjects and ensure visual clarity. The final result shows that a solid understanding and effective application of these techniques can strengthen the human interest aspect and create engaging, emotionally impactful visuals. In conclusion, the appropriate use of cinematographic techniques significantly enhances storytelling in feature videos, making them a powerful medium for voicing social issues.